2019
DOI: 10.1007/978-3-030-31514-6_13
|View full text |Cite
|
Sign up to set email alerts
|

Conformal Predictions for Hybrid System State Classification

Abstract: Neural State Classification (NSC) [19] is a scalable method for the analysis of hybrid systems, which consists in learning a neural network-based classifier able to detect whether or not an unsafe state can be reached from a certain configuration of a hybrid system. NSC has very high accuracy, yet it is prone to prediction errors that can affect system safety. To overcome this limitation, we present a method, based on the theory of conformal prediction, that complements NSC predictions with statistically sound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
1
1
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…In [8], we presented a preliminary version of this approach. The present paper greatly extends and improves that work by including an automated and optimal method to select rejection thresholds, the active learning method, and an evaluation on larger HA benchmarks.…”
Section: Related Workmentioning
confidence: 99%
“…In [8], we presented a preliminary version of this approach. The present paper greatly extends and improves that work by including an automated and optimal method to select rejection thresholds, the active learning method, and an evaluation on larger HA benchmarks.…”
Section: Related Workmentioning
confidence: 99%
“…For example, in a binary classification problem, one can consider the difference between the probability of the two classes as a measure of uncertainty, where small differences indicate uncertain predictions. Previous experiments in [29] have shown that such a measure yields poor error detection in NPM, because the measure is overconfident in predictions that turn out being erroneous.…”
Section: Remark 3 (Softmax Probabilities As Uncertainty Measures)mentioning
confidence: 99%
“…In [29], we presented a preliminary version of the frequentist approach. In [10], we added to it an automated and optimal method to select the rejection thresholds and an active learning framework.…”
Section: Related Workmentioning
confidence: 99%